Prototipe Pemanas Air Tenaga Surya Menggunakan Karbon Sebagai Penampung Kalor - Wihantoro, Wihantoro; Yanto, Agus; Sunardi, Sunardi (BERKALA FISIKA, 2010)
A solar water heater prototype that fully exploit the nature of black body radiation are made from carbon powder mixed with cement as a thermal energy container material has been created. The phenomenon of physics that underlie the pattern of spread of heat and decrease their physical equations studied in this paper.Construction of heating a metal box containing the installation of planar spiral-shaped copper pipe which is covered with mortar-carbon. The water that fills the copper pipes are supplied by thermal energy from carbon-mortar. Immediately after absorbing heat energy, water density to be different in each section of pipe, causing water circulation by convection between the heater with a water reservoir. The performance of prototype heater is seen from measurements of water temperature rise in the reservoir every 15 minutes. The results are used to determine the average temperature rise of water in every second of it at once to calculate heat energy absorbed by the water in each second. Water temperature in the reservoir increased by 0.0009 ° C per second. At the maximum irradiation conditions, the rate of heat per second that are transferred from a mixture of carbon into the water-cement amounted to 0.075 kW. Keywords: heat energy, water circulation by convection, heat rate per second